Identification of polyphenols from antiviral Chamaecrista nictitans extract using high-resolution LC–ESI–MS/MS - Mateos Martín, María Luisa (2014)
Chamaecrista nictitans (L) extract possesses antiviral properties; it acts against the herpes simplex virus, and this may be attributed to its constituent phenolics. Here, high-resolution LC–ESI–MS/MS is used to identify the phenolic components of the most potent fraction of the extract. The fraction is a complex mixture rich in oligomeric proanthocyanidins with a high content of monohydroxyphenol moieties ((epi)fisetinidol, (epi)afzelechin and (epi)guibourtinidol) and A-type linkages, uncommon in other proanthocyanidin-rich phenolic extracts, such as those from grape seeds or pine bark. As monohydroxyphenolic structures and A-type linkages have been related to antiviral effects, particularly through the inhibition of late transcription, we suggest that the fraction of C. nictitans extract exerts its action through a particularly effective combination of proanthocyanidins that include these two structural features.